Mengintegrasikan Budaya Longko’ Torayan melalui Praktik Pendidikan Berbasis Kearifan Lokal di Sekolah - Bawan, Yustus; Leonardo, Noldy Ferry; Salamba, Efraim; Melianus (PEADA': Jurnal Pendidikan Kristen, 2024)
This research aims to integrate Longko' Torayan culture with education practices based on local wisdom in schools. Longko' Torayan is a cultural heritage of the Toraja ancestors, which is literally interpreted as the culture of shame. However, this culture is also rich in meaning, emphasizing inclusive values as the foundation of communal life in society. The research method used is a qualitative ethnographic approach. Data collection was obtained through literature studies to understand Longko' Torayan culture. The research results show that the cultural values of Longko' Torayan are not just about the culture of shame but also teach the meanings of loyalty, kinship, honor, maintaining family dignity, tolerance, and work ethic, which can serve as the foundation in educational practices in schools and as a means to introduce, respect, and preserve Toraja culture. The integration of Longko' Torayan cultural wisdom in education can be implemented through curriculum development that includes theory and practice in schools. Thus, this research is expected to provide a foundation for the development of educational practices based on local wisdom in schools, encouraging students to understand, appreciate, and implement the values of Longko' Torayan local wisdom, both in schools and in communal life in society.